Penerapan Teori Keperawatan Comfort Katharine Kolcaba dalam Pemberian Asuhan Keperawatan Perioperatif - Zulkifli B. Pomalango (Jurnal Anestesi, 2023)
The use of Kolcaba's theory of comfort is easy to apply in the perioperative field and is useful for addressing a variety of patient comfort needs. Fulfillment of holistic comfort through indicators of relief (freedom), ease (calmness), transcendence (happiness). This literature review was carried out by collecting articles and textbooks from databases such as Proquest, Scient Direct, Google Search, Google Scholar. The search was carried out using the keywords "Comfort", "Katherin Kolcaba", "Nurse" and "Perioperative". The selected article focuses on Katharine Kolcaba's practice theory of Comfort in Perioperative Care. The results of the study show that the theory of comfort is very helpful in providing nursing care for perioperative patients, through feeling comfortable facilitating the emergence of synergistic, multidimensional, organismal responses that can influence the healing process. So that the theory of comfort is highly recommended in providing nursing interventions for perioperative patients. Nursing interventions in the four holistic contexts lead to various ways to help patients find relief, serenity or transcendence. Using comfort theory can assist nurses in assessing and identifying patient needs and in providing nursing interventions.